2016
DOI: 10.1001/jama.2016.4218
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity of Novel Adenovirus Type 26– and Modified Vaccinia Ankara–Vectored Ebola Vaccines

Abstract: IMPORTANCE Developing effective vaccines against Ebola virus is a global priority. OBJECTIVE To evaluate an adenovirus type 26 vector vaccine encoding Ebola glycoprotein (Ad26.ZEBOV) and a modified vaccinia Ankara vector vaccine, encoding glycoproteins from Ebola virus, Sudan virus, Marburg virus, and Tai Forest virus nucleoprotein (MVA-BN-Filo). DESIGN, SETTING, AND PARTICIPANTS Single-center, randomized, placebo-controlled, observer-blind, phase 1 trial performed in Oxford, United Kingdom, enrolling healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
290
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 294 publications
(312 citation statements)
references
References 26 publications
(25 reference statements)
15
290
0
7
Order By: Relevance
“…Vaccines that were assessed in phase I and/or II studies during the 2013-2016 EBOV epidemic include rVSV-EBOV [268][269][270][271][272] , Ad5-EBOV [273][274][275] , rVSV-EBOV combined with rAd5-EBOV 276 , ChAd3-EBOV with or without MVA-EBOV [277][278][279][280] , Ad26-EBOV combined with MVA-EBOV 281 , and DNA encoding multiple filovirus GPs 282,283 . These EBOV vaccines generally elicited good immunogenicity against EBOV GP, and no serious adverse events were described.…”
Section: Vaccination Of Humansmentioning
confidence: 99%
“…Vaccines that were assessed in phase I and/or II studies during the 2013-2016 EBOV epidemic include rVSV-EBOV [268][269][270][271][272] , Ad5-EBOV [273][274][275] , rVSV-EBOV combined with rAd5-EBOV 276 , ChAd3-EBOV with or without MVA-EBOV [277][278][279][280] , Ad26-EBOV combined with MVA-EBOV 281 , and DNA encoding multiple filovirus GPs 282,283 . These EBOV vaccines generally elicited good immunogenicity against EBOV GP, and no serious adverse events were described.…”
Section: Vaccination Of Humansmentioning
confidence: 99%
“…Moreover, boosting with the heterologous vaccine could prolong durability of protective immunity and induce stronger immune response to antigens than using homogeneous vaccination, which was shown in different clinical trials and suggested as a prospective approach of vaccination by WHO experts. 30,33,37 In the past decade, we have witnessed impressive progress in the development of viral vectored vaccine. Recombinant viral vectors are good at delivering heterologous antigens that combine the different favorable features of other vaccine modalities, with minimal disadvantages.…”
Section: Discussionmentioning
confidence: 99%
“…A single-center, randomized, placebocontrolled, observer-blind, phase I trial adopting prime-boost regimen (prime with Ad26-EBOV or MVA-BN Filo and boost with the alternative vaccine 28 or 56 d later) enrolled 87 participants to evaluate the safety and immunogenicity of the Ad26-EBOV (Table 4). 30 Mild to moderate injection-site pain was the 31 Two outstanding advantages of this Ad5-EBOV was noticed: first, the Ad5-EBOV is the first Ebola vaccine developed according to the 2014 epidemic strain, which was considered to be a new epidemic strain, with 96.7% homology of the nucleotide sequence and 97.6% homology of amino acid sequence 31 compared to the GP gene of the strain in 1976 which was based on by other vaccines; 32,33 Second, the Ad5-EBOV is lyophilized white powder (can be stored at 2-8 C), which may be more suitable for the areas where the cold chain system is incomplete than those liquid formulations. After a preliminary efficacy was observed in the pre-clinical animal studies, the Ad5-EBOV was quickly put into the clinical trials at the end of 2014 ( Table 1).…”
Section: Non-replicative Vector-based Ebola Vaccinesmentioning
confidence: 99%
“…Contains antigen АМА-1 (apical membrane antigen -1) [16]. Для данного типа вакцин заявлены уже 3 и 4 фаза исследова-ний, которые планируется проводить не только на здоровых добровольцах, но и людях с ВИЧ-инфекцией, пожилых людях, детях, в том чис-ле рожденных у участников предыдущих этапов исследований.…”
Section: вакцины на основе ад-векторовunclassified